Sintesis Karbon Aktif dari Kulit Pisang untuk Pemurnian Air Tambang Emas di Sungai Batang Palangki Kabupaten Sijunjung dari Logam Berat - rahmah khairati maiza; Melanz Hasan; Muhammad Fadly; A Astuti (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2019)
The purification of waste water from the gold mine from heavy metals in Batang Palangki, Sijunjung Regency has been carried out. Prior to the purification of this wastewater, water samples were first measured by heavy metal content using Inductively Coupled Plasma (ICP) and found 24 heavy metal elements of which 8 of them were above the standard threshold of water quality standards. Purification of water using adsorption technique with adsorbent activated carbon from banana kepok skin. This study used activated carbon with concentration concentration of 20%, 25%, 30%, and 35% H2SO4 activator. Activated carbons were added to the measuring cup containing 100 ml of gold mine waste water, stirred to homogeneous and allowed to settle to the bottom of the measuring cup, then filtered water using filter paper, measured pH, heavy metal content and electrical conductivity values. Based on the research results, activated carbon with the most optimal absorption is at concentration of 35% with the average pore size of activated carbon of 24.6 um. This data was obtained from the Inductively Coupled Plasma (ICP) tool by comparing the heavy metal content of wastewater before and after the activated carbon treatment. The purified water is in accordance with Minister of Health Regulation no. 416 / MENKES / PER / IX / 1990 on water quality requirements and Government Regulation no. 82 of 2001 on the Management of Water Quality and Control of Water Pollution.